The Effect of Perceived Value, Brand Image, Satisfaction, Trust and Commitment on Loyalty at XYZ Hospitals, Tangerang - Anggreini Oktavia Trisno; Margaretha Pink Berlianto (Jurnal Manajemen Kesehatan Indonesia, 2023)
Patient loyalty is a significant aspect of marketing strategies in the health industry, including hospitals. Loyal patients will return for treatment and recommend the hospital to others, and this can reduce marketing expenditure. Patient loyalty can be influenced by several factors, such as satisfaction, perceived value, commitment, trust, and brand image. If the patient's necessity meets their expectation, they will be loyal to the hospital. This study aims to find the positive effect of the independent variable, in the form of perceived value and brand image, towards the dependent variable, i.e., loyalty. Furthermore, the mediating variables are trust, commitment, and satisfaction, which can affect loyalty in private hospitals accredited by KARS and JCI. This research was conducted by distributing questionnaires via a google form. The data collected in this study were 261 respondents treated at XYZ Hospital, using a purposive sampling technique. The data in this study were analyzed using partial lease square-structural equation modeling (PLS-SEM) with the SmartPLS application. The results of this study showed that brand image, commitment, and satisfaction have a positive impact on loyalty; the brand image has a positive impact on satisfaction; Perceived value has a positive impact on trust and satisfaction; satisfaction has a positive impact on trust and commitment. Moreover, perceived value and trust do not demonstrate a positive impact on the study.